Shaping Clinical Policy for Salvage Radiotherapy After Radical Prostatectomy in Prostate Cancer: Bridging the Gap Between Clinical Trials and Daily Practice - Piero Bettoli; Evangelina Röling; Moises Russo; María Fernanda Sánchez; Inti Paredes; Jorge Sapunar (Cancer Medicine)
ABSTRACT Purpose and Objective Salvage radiotherapy (sRT) can have similar outcomes to adjuvant radiotherapy (aRT) if administered at the earliest evidence of biochemical recurrence. RADICALS‐RT was the first trial to support this hypothesis and a policy of observation after radical prostatectomy (RP) with early sRT has become the new standard of care since then. This study assessed the impact of RADICALS‐RT in the clinical practice regarding the timing of sRT for prostate cancer initially treated with RP. Methods Data from 297 patients who underwent sRT after radical RP were retrospectively collected. Two groups were created and analyzed on the basis of the date of RADICALS‐RT presentation at ESMO. After these results were released in October 2021, our institutional postoperative radiotherapy policy was revisited, and a third group was created and analyzed separately. Results Median PSA for Groups 1, 2, and 3 were 0.33, 0.27, and 0.2, respectively. Less than one‐third of patients in Groups 1 and 2 had a postoperative PSA of 0.2 ng/mL or less at the time of sRT. Group 3 showed statistically significant differences in median PSA at the time of sRT compared with Groups 1 and 2. Conclusions RADICALS‐RT demonstrated a significant impact on clinical practice only after being complemented with real local evidence.